Anti-inflammatory properties of ursodeoxycholyl lysophosphatidylethanolamide in endotoxin-mediated inflammatory liver injury. - Johannes Maximilian Ludwig; Yuling Zhang; Walee Chamulitrat; Wolfgang Stremmel; Anita Pathil (PLoS ONE, 2018)
AIM:Endotoxin-mediated liver inflammation is a key component of many acute and chronic liver diseases contributing to liver damage, fibrosis and eventually organ failure. Here, we investigated ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE), a synthetic bile acid-phospholipid conjugate regarding its anti-inflammatory and anti-fibrogenic properties. METHODS:Anti-inflammatory properties of UDCA-LPE were evaluated in a mouse model of D-galactosamine/lipopolysaccharide (GalN/LPS)-induced acute liver injury, LPS treated RAW264.7 macrophages and murine primary Kupffer cells. Furthermore, anti-inflammatory and anti-fibrotic effects of UDCA-LPE were studied on primary hepatic stellate cells (HSC) incubated with supernatant from LPS±UDCA-LPE treated RAW264.7 cells. RESULTS:UDCA-LPE ameliorated LPS-induced increase of IL-6, TNF-α, TGF-β, NOX-2 in the GalN/LPS model by up to 80.2% for IL-6. Similarly, UDCA-LPE markedly decreased the expression of inflammatory cytokines IL-6, TNF-α and TGF-β as well as the chemokines MCP1 and RANTES in LPS-stimulated RAW 264.7 cells. Anti-inflammatory effects were also observed in primary murine Kupffer cells. Mechanistic evaluation revealed a reversion of LPS-activated pro-inflammatory TLR4 pathway by UDCA-LPE. Moreover, UDCA-LPE inhibited iNOS and NOX-2 expression while activating eNOS via phosphorylation of AKT and pERK1/2 in RAW264.7 cells. HSC treated with conditioned medium from LPS±UDCA-LPE RAW264.7 cells showed lower fibrogenic activation due to less SMAD2/3 phosphorylation, reduced expression of profibrogenic CTGF and reduced pro-inflammatory chemokine expression. CONCLUSION:In the setting of endotoxin-mediated liver inflammation, UDCA-LPE exerts profound anti-inflammatory and anti-fibrotic effect implying a promising potential for the drug candidate as an experimental approach for the treatment of acute and chronic liver diseases.